Spatial dynamics of filamentous soil fungi in response to a heterogeneously distributed chemical stressor - Catharina Neumann; Miloš Bielčik; Matthias C. Rillig (Fungal Ecology, 2026)

Unravelling cumulative effects of human pressures on demersal fish traits using a driver-pressure-state-impact framework - Jennifer Rehren; W. Nikolaus Probst; Casper Kraan; Hermann Neumann; Shubham Krishna; Matthias Hasenbein; Serra Örey; Kim Ludwig; Kai W. Wirtz; Carsten Lemmen; Antje Gimpel; Vanessa Stelzenmüller (Marine Environmental Research, 2026)

Predicting Air Flow in Calendered Paper Sheets from μ-CT Data: Combining Physics with Morphology - Phillip Gräfensteiner; Andoni Rodriguez; Peter Leitl; Ekaterina Baikova; Maximilian Fuchs; Eduardo Machado Charry; Ulrich Hirn; André Hilger; Ingo Manke; Robert Schennach; Matthias Neumann; Volker Schmidt; et al. (Transport in Porous Media, 2026)
Predicting the macroscopic properties of thin fiber-based porous materials from their microscopic morphology remains challenging because of the structural heterogeneity of these materials. In this study, computational fluid dynamics simulations were performed to compute volume air flow based on tomographic image data of uncompressed and compressed paper sheets. To reduce computational demands, a pore network model was employed, allowing volume air flow to be approximated with less computational effort. To improve prediction accuracy, geometric descriptors of the pore space, such as porosity, surface area, median pore radius, and geodesic tortuosity, were combined with predictions of the pore network model. This integrated approach significantly improves the predictive power of the pore network model and indicates which aspects of the pore space morphology are not accurately represented within the pore network model. In particular, we illustrate that a high correlation among descriptors does not necessarily imply redundancy in a combined prediction.

Drivers of Viral Prevalence in Landscape‐Scale Pollinator Networks Across Europe: Honey Bee Viral Density, Niche Overlap With This Reservoir Host and Network Architecture - Willem Proesmans; Cedric Alaux; Matthias Albrecht; Karima Bassit; Nathan Cyrille; Anne Dalmon; Virginie Diévart; Christophe Dominik; Emeline Felten; Anna Gajda; Jonna M. Heuschele; Emilien Laurent; et al. (Ecology Letters, 2026)
Viral transfer from managed pollinators potentially threatens wild pollinators and may be exacerbated by land‐use changes. Our causal models and plant‐pollinator network data from 48 European urban and agricultural landscapes revealed the ecological mechanisms underpinning viral transmission. Host identity, network architecture and land‐use modulated viral dynamics (black queen cell virus, BQCV; deformed wing virus, DWV‐A and DWV‐B). Viral prevalence in wild pollinators was driven by viral density in the reservoir host: honey bees, and secondarily by trophic niche overlap with these managed pollinators. Modular networks limited BQCV prevalence, which was driven by reduced honey bee niche overlap, suggesting minimal onward transmission among wild pollinators. Landscapes supporting greater wild pollinator abundance diluted DWV‐B transmission; in urban landscapes managed honey bees and wild pollinators experienced higher and lower BQCV prevalence, respectively. Disease in managed bee colonies and land‐use changes that concentrate pollinator foraging interactions present potential viral risks to wild pollinator health.

Genome-wide association study of Fuchs’ endothelial corneal dystrophy in the German population - Juliane Fechner; Guilherme B. Neumann; Fabia Murza; Leonard Matthias; Marcus Walckling; Claudia Brockmann; Thomas A. Fuchsluger; Tobias Brockmann (Human Genetics, 2025)
The genetic etiology of Fuchs Endothelial Corneal Dystrophy (FECD) is not yet fully elucidated. While the disease is widespread and the leading indication for corneal transplantation in the Western world, the concurrent shortage of corneal transplants underscores the urgent need for further research into the underlying mechanisms. Such investigations could enable the development of innovative therapeutic strategies. Therefore, we aimed to verify candidate genes previously identified and sought after novel variants in the German population. Undertaking a genome wide association study (GWAS) using the Axiom™ Precision Medicine Diversity Array on 157 FECD cases and 309 controls, followed by pathway enrichment analysis, we were able to confirm the significance of the TCF4 locus (rs613872, p = 8.0 × 10 − 23 , OR = 8.60, h 2 = 0.72) and identified a range of novel variants. Further fine-mapping highlighted novel candidate SNPs, such as on chromosome 5 in the SEMA6A gene (rs153643, p = 3.1 × 10 − 9 , OR = 2.75, h 2 = 0.30), and on chromosome 19 in the DNAJC19P3 gene (rs62117964, p = 3.3 × 10 − 8 , OR = 3.61, h 2 = 0.29). SEMA6A gene is involved in apoptotic pathways and cytoskeletal remodeling, making it an interesting candidate gene for further investigations as a potential therapeutic target. Furthermore, several variants were identified in lncRNAs, which presumably influence the expression of nearby protein-coding genes. For example, LOC105372130 , which is associated with corneal hysteresis and corneal resistance factor, may influence the expression of TCF4 .

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Joint Distributions of Local Pore Space Properties Quantitatively Explain Simulated Air Flow Variations in Paper - Peter Leitl; Eduardo Machado Charry; Ekaterina Baikova; Matthias Neumann; Ulrich Hirn; Volker Schmidt; Karin Zojer (Transport in Porous Media, 2023)
The gas flow through sheet-like porous materials such as paper can show marked lateral variations due to a heterogeneous, locally varying microstructure. Hence, reliable predictions of such lateral flux variations require an appropriate consideration of local variations in the microstructure. The flow through such sheet-like materials is commonly described with Darcy’s law in which permeances are formulated in terms of microstructure properties, such as porosities, tortuosities, or hydraulic radii. This work proposes an extension of existing permeance models that directly considers the variation and the cross-dependence between local microstructure properties. The extended model is applied to local air fluxes through a paper sheet to exemplarily reveal the joint impact of local porosities and local tortuosities on the air flux. The key extension is to consider a joint distribution of porosity and tortuosity. The latter is constructed from the univariate property distributions using a copula approach and yields local tortuosities including their variation for any encountered local porosity. These values jointly enter any permeance model that qualitatively captures the dependence of the air flux on the porosity. To assess the merit of the model, variations in the air flux and in the pore space properties are independently determined from the same measured microstructure of paper. Air flux variations are provided by computational fluid dynamics simulations on multiple, nonoverlapping segments taken from the microstructure. A statistical analysis of the entire microstructure provides the distribution of local porosity, tortuosity, and thicknesses. Our model quantitatively explains that porosity-dependent variations in the tortuosity, in particular the ones associated with high-volume pathways, decisively determine air flux variations.

Detection of Colchicum autumnale in drone images, using a machine-learning approach - Lukas Petrich; Georg Lohrmann; Matthias Neumann; Fabio Martin; Andreas Frey; Albert Stoll; Volker Schmidt (Precision Agriculture, 2020)
Colchicum autumnale are toxic autumn-blooming flowering plants, which often grow on extensive meadows and pastures. Thus, they pose a threat to farm animals especially in hay and silage. Intensive grassland management or the use of herbicides could reduce these weeds but environment protection requirements often prohibit these measures. For this reason, a non-chemical site- or plant-specific weed control is sought, which aims only at a small area around the C. autumnale and with low impact on the surrounding flora and fauna. For this purpose, however, the exact locations of the plants must be known. In the present paper, a procedure to locate blooming C. autumnale in high-resolution drone images in the visible light range is presented. This approach relies on convolutional neural networks to detect the flower positions. The training data, which is based on hand-labeled images, is further enhanced through image augmentation. The quality of the detection was evaluated in particular for grassland sites which were not included in the training to get an estimate for how well the detector works on previously unseen sites. In this case, 88.6% of the flowers in the test dataset were detected, which makes it suitable, e.g., for applications where the training is performed by the manufacturer of an automatic treatment tool and where the practitioners apply it to their previously unseen grassland sites.

Ventilation of the northern Baltic Sea - Thomas Neumann; Herbert Siegel; Matthias Moros; Monika Gerth; Madline Kniebusch; Daniel Heydebreck (Ocean Science, 2020)
The Baltic Sea is a semi-enclosed, brackish water sea in northern Europe. The deep basins of the central Baltic Sea regularly show hypoxic conditions. In contrast, the northern parts of the Baltic Sea, the Bothnian Sea and Bothnian Bay, are well oxygenated. Lateral inflows or a ventilation due to convection are possible mechanisms for high oxygen concentrations in the deep water of the northern Baltic Sea. In March 2017, conductivity–temperature–depth (CTD) profiles and bottle samples, ice core samples, and brine were collected in the Bothnian Bay. In addition to hydrographic standard parameters, light absorption has been measured in all samples. A complementary numerical model simulation provides quantitative estimates of the spread of newly formed bottom water. The model uses passive and age tracers to identify and trace different water masses. Observations indicate a recent ventilation of the deep bottom water at one of the observed stations. The analysis of observations and model simulations shows that the Bothnian Bay is ventilated by dense water formed due to mixing of Bothnian Sea and Bothnian Bay surface water initializing lateral inflows. The observations show the beginning of the inflow and the model simulation demonstrates the further northward spreading of bottom water. These events occur during wintertime when the water temperature is low. Brine rejected during ice formation barely contributes to dense bottom water.

Quantifying the contribution of shipping NO x emissions to the marine nitrogen inventory – a case study for the western Baltic Sea - Daniel Neumann; Matthias Karl; Hagen Radtke; Volker Matthias; René Friedland; Thomas Neumann (Ocean Science, 2020)
The western Baltic Sea is impacted by various anthropogenic activities and stressed by high riverine and atmospheric nutrient loads. Atmospheric deposition accounts for up to a third of the nitrogen input into the Baltic Sea and contributes to eutrophication. Amongst other emission sources, the shipping sector is a relevant contributor to the atmospheric concentrations of nitrogen oxides (NOX) in marine regions. Thus, it also contributes to atmospheric deposition of bioavailable oxidized nitrogen into the Baltic Sea. In this study, the contribution of shipping emissions to the nitrogen budget in the western Baltic Sea is evaluated with the coupled three-dimensional physical biogeochemical model MOM–ERGOM (Modular Ocean Model–Ecological ReGional Ocean Model) in order to assess the relevance of shipping emissions for eutrophication. The atmospheric input of bioavailable nitrogen impacts eutrophication differently depending on the time and place of input. The shipping sector contributes up to 5 % to the total nitrogen concentrations in the water. The impact of shipping-related nitrogen is highest in the offshore regions distant from the coast in early summer, but its contribution is considerably reduced during blooms of cyanobacteria in late summer because the cyanobacteria fix molecular nitrogen. Although absolute shipping-related total nitrogen concentrations are high in some coastal regions, the relative contribution of the shipping sector is low in the vicinity of the coast because of high riverine nutrient loads.

Assessment of Uncertainties in Scenario Simulations of Biogeochemical Cycles in the Baltic Sea - H. E. Markus Meier; Moa Edman; Kari Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2019)

Assessment of Eutrophication Abatement Scenarios for the Baltic Sea by Multi-Model Ensemble Simulations - H. E. Markus Meier; Moa K. Edman; Kari J. Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2018)

Effect of ultraviolet photofunctionalization of dental titanium implants on osseointegration - Christian Mehl; Matthias Kern; Friederike Neumann; Telse Bähr; Jörg Wiltfang; Volker Gassling (Journal of Zhejiang University-SCIENCE B, 2018)

Different utilization of alginate and other algal polysaccharides by marine A lteromonas macleodii ecotypes - Anna M. Neumann; John P. Balmonte; Martine Berger; Helge‐Ansgar Giebel; Carol Arnosti; Sonja Voget; Meinhard Simon; Thorsten Brinkhoff; Matthias Wietz (Environmental Microbiology, 2015)
Summary The marine bacterium A lteromonas macleodii is a copiotrophic r ‐strategist, but little is known about its potential to degrade polysaccharides. Here, we studied the degradation of alginate and other algal polysaccharides by A . macleodii strain 83‐1 in comparison to other A . macleodii strains. Cell densities of strain 83‐1 with alginate as sole carbon source were comparable to those with glucose, but the exponential phase was delayed. The genome of 83‐1 was found to harbour an alginolytic system comprising five alginate lyases, whose expression was induced by alginate. The alginolytic system contains additional CAZ ymes, including two TonB ‐dependent receptors, and is part of a 24 kb genomic island unique to the A . macleodii ‘ surface clade’ ecotype. In contrast, strains of the ‘deep clade’ ecotype contain only a single alginate lyase in a separate 7 kb island. This difference was reflected in an eightfold greater efficiency of surface clade strains to grow on alginate. Strain 83‐1 furthermore hydrolysed laminarin, pullulan and xylan, and corresponding polysaccharide utilization loci were detected in the genome. A lteromonas macleodii alginate lyases were predominantly detected in Atlantic Ocean metagenomes. The demonstrated hydrolytic capacities are likely of ecological relevance and represent another level of adaptation among A . macleodii ecotypes.

Echoes from the Past: A Healthy Baltic Sea Requires More Effort - Aarno T. Kotilainen; Laura Arppe; Slawomir Dobosz; Eystein Jansen; Karoline Kabel; Juha Karhu; Mia M. Kotilainen; Antoon Kuijpers; Bryan C. Lougheed; H. E. Markus Meier; Matthias Moros; Thomas Neumann; et al. (Ambio, 2014)

Spatio-temporal overlap of the alien invasive ctenophore Mnemiopsis leidyi and ichthyoplankton in the Bornholm Basin (Baltic Sea) - Matthias Schaber; Holger Haslob; Bastian Huwer; Anne Harjes; Hans-Harald Hinrichsen; Marie Storr-Paulsen; Jörn O. Schmidt; Rüdiger Voss; Viola Neumann; Friedrich W. Köster (Biological Invasions, 2011)

On the Photophysical Properties of New Luminol Derivatives and their Synthetic Phthalimide Precursors - Raúl Pérez-Ruiz; Robert Fichtler; Yrene Diaz Miara; Matthieu Nicoul; Dominik Schaniel; Helfried Neumann; Matthias Beller; Dirk Blunk; Axel G. Griesbeck; Axel Jacobi von Wangelin (Journal of Fluorescence, 2010)